2022
DOI: 10.3390/land11101707
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Hydrological Connectivity Evaluation of Tidal Creeks in Coastal Wetlands

Abstract: Tidal creeks play a critical role in delivering water, suspended sediments, and nutrients to coastal wetlands, so it is important to understand the characteristics of the tidal creek system to guide the development and sustainable utilization of coastal wetlands. Using the coastal wetlands of the Liao River Estuary (LRE) as a study area, this study accurately divided the tidal flat based on the principle of tidal correction, extracted the linear features of tidal creeks using high-resolution remote sensing (RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Remote sensing satellite image data have been increasingly useful for studying the relationship between vegetation and tidal creeks, as well as for establishing morphological characteristic indices in the presence of hydrological connectivity [11]. Recent studies suggested that the tidal gullies and wetland vegetation are interrelated [12,13]. The relationship between tidal creeks and vegetation distribution pattern in the Yangtze River delta, Yancheng nature reserve, and Yellow River delta has been established by examining the drainage efficiency of vegetation-free and vegetation-covered tidal creek networks, the evolution of tidal creeks, and the expansion of Spartina alterniflora [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing satellite image data have been increasingly useful for studying the relationship between vegetation and tidal creeks, as well as for establishing morphological characteristic indices in the presence of hydrological connectivity [11]. Recent studies suggested that the tidal gullies and wetland vegetation are interrelated [12,13]. The relationship between tidal creeks and vegetation distribution pattern in the Yangtze River delta, Yancheng nature reserve, and Yellow River delta has been established by examining the drainage efficiency of vegetation-free and vegetation-covered tidal creek networks, the evolution of tidal creeks, and the expansion of Spartina alterniflora [14][15][16].…”
Section: Introductionmentioning
confidence: 99%